2009
DOI: 10.1192/bjp.bp.107.045633
|View full text |Cite
|
Sign up to set email alerts
|

Structural and metabolic changes in language areas linked to formal thought disorder

Abstract: BackgroundThe role of the language network in the pathophysiology of formal thought disorder has yet to be elucidated.AimsTo investigate whether specific grey-matter deficits in schizophrenic formal thought disorder correlate with resting perfusion in the left-sided language network.MethodWe investigated 13 right-handed patients with schizophrenia and formal thought disorder of varying severity and 13 matched healthy controls, using voxel-based morphometry and magnetic resonance imaging perfusion measurement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 48 publications
11
103
0
8
Order By: Relevance
“…Also, studies using positron emission tomography 56 and functional magnetic resonance imaging 57,58 correlate left STG with FTD, being thus consistent with structural findings.…”
Section: Formal Thought Disorder Is Associated With Structural and Fusupporting
confidence: 74%
“…Also, studies using positron emission tomography 56 and functional magnetic resonance imaging 57,58 correlate left STG with FTD, being thus consistent with structural findings.…”
Section: Formal Thought Disorder Is Associated With Structural and Fusupporting
confidence: 74%
“…No qualitative distinctions were found between different ASL techniques. All the articles reported significant differences between schizophrenia patients and healthy controls, except for the one by Horn et al 13 , which was the only study to find no differences in rCBF between patients and controls (although the authors found a positive correlation between formal thought disorder and rCBF). It should be mentioned here that the study by Horn et al 13 did not acquire images from superior regions of the brain because of technical limitations.…”
Section: Convergent Resultsmentioning
confidence: 86%
“…Most studies of resting perfusion in patients with schizophrenia spectrum disorders relative to healthy controls, thus, focused predominantly on the hippocampal region. Overall, these studies reported seemingly mixed results, including increases (Friston, Liddle, Frith, Hirsch, & Frackowiak, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014; Talati, Rane, Skinner, Gore, & Heckers, 2015), decreases (Kindler et al, 2015; Nordahl et al, 1996; Scheef et al, 2010; Tamminga et al, 1992), or no differences (Horn et al, 2009; Ota et al, 2014; Vita et al, 1995). Beyond the hippocampus, other brain regions of significantly elevated resting perfusion in schizophrenia patients compared with healthy controls have involved the basal ganglia and middle temporal lobes (Pinkham et al, 2011), cerebellum, brainstem, and thalamus (Scheef et al, 2010).…”
Section: Introductionmentioning
confidence: 99%